Ανακύκλωση αλουμινίου (Ministry Environment & Energy, 2012)
: What is it, youth? Are you kidding? Gasoline, of course. Before the High Court has you executed, you should be made to watch what happens when we return here with the Gargons. By the elements alone, they will grow to millions of times their original size, in less time than it takes for the... ...ugly new plot against... For every box of aluminium, we need as much energy as a TV in two hours. Think before you throw it away. Aluminium is not trash.